The effect of tocotrienol-rich fraction supplementation on the ovarian metabolome and the quality of oocyte in aging mice - Norrabiátul Adawiyah A,; Teh, LK; Fathimah M,; Nuraliza AS, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Ovarian aging has been associated with oxidative stress and loss of ovarian function. Tocotrienol has been proven to exert beneficial effects on the female reproductive system. However, the role of tocotrienol in affecting metabolism in the ovary and subsequently improving the quality of oocytes in aging mice remains unknown. Therefore, the relationship between metabolic changes in the ovary and the quality of oocytes in aging mice following tocotrienol-rich fraction (TRF) supplementation was investigated. Six-week-old female mice were used as the Young group. Six-month-old aged female mice were divided into four groups; the first group was given tocopherol-stripped corn oil (vehicle control) while the other three groups were supplemented with TRF at the dose of 90, 120, and 150 mg/kg, respectively. The treatment was given orally for two months. At the end of the treatment, mice from all groups were superovulated and then euthanised. Oocyte quality was assessed and non-targeted metabolomic analysis of the ovarian tissues was performed using liquid chromatography-tandem mass spectrometry of quadrupole time-of-flight (LC-MS Q-TOF). Percentages of normal oocytes were higher (p<0.001) while abnormal oocytes were lower (p<0.001) in TRF 150 mg/kg group compared to that of the control. Seventeen metabolites were identified to be significantly different in the ovarian tissue of the aging group when compared to the young group. 14 metabolites were identified to be significantly different in the ovarian tissue between the control and TRF supplemented groups. Pathway analysis revealed significantly altered metabolic pathways for fatty acid and amino acid metabolism that might influence the quality of oocytes. In conclusion, TRF supplementation causes metabolic changes in the ovary that delay the consequences of aging, thus improving the quality of oocytes in aging mice.